Perioperative Cannabis as a Potential Solution for Reducing Opioid and Benzodiazepine Dependence - Stewart, Camille; Fong, Yuman (JAMA surgery, 2021)
IMPORTANCE: Cannabis is increasingly being used for medicinal purposes but remains outside Western medical practice. Data on perioperative use and outcomes are scarce. Few surgeons receive training regarding legal endorsement, reported medicinal benefits, and potential risks, making it difficult to advise patients. Guidelines and additional research are needed. OBSERVATIONS: It is legal to recommend cannabis, which can be obtained in states with medical cannabis programs. There are many methods of consumption, oral being the safest. Activity is primarily through Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) via cannabinoid receptors, which may be potentiated when taken together in the plant or plant extract. The known effects of cannabis on inflammation and malignancy are largely limited to laboratory experiments. However, there are higher-quality data to support adjunctive use of cannabis for relief of pain, nausea, and insomnia, which may be useful postoperatively and could potentially decrease reliance on opiates and benzodiazepines. There are prospective trials in surgical patients, but no reported data regarding surgical complications or other surgical outcomes. Currently, cannabis is regulated differently than other controlled substances, and there are issues with purity/homogeneity, making it difficult for surgeons to accept or significantly explore its medical benefits. CONCLUSIONS AND RELEVANCE: Recommendations are made for surgeons advising patients who use cannabis based on the limited existing data. While cannabis likely has some therapeutic benefits, it must be treated as other medical controlled substances to truly elucidate its role in surgical patient care.